Research on Key Technologies of Power Internet of Things Based on Artificial Intelligence Technology. Issue 4 (March 2021) - Lin, Xiaokang; Lin, Jianeng; Su, Zhiyong; Lin, Chengchang
Abstract: Abstract: With the development of science and technology, the power industry has combined many new technologies driven by science and technology to improve its own operating quality. The Internet of Things is a new technology that can significantly improve the power system. This article aims to study the key technologies of power Internet of Things based on artificial intelligence technology. This paper takes the research of intelligent meter reading system as an example, and conducts experimental analysis based on artificial intelligence algorithms. Using artificial algorithms in the spider web network topology, as the network increases, the communication paths that can be selected between nodes also increase, and the full-end reliability of the network topology also increases. The collection node is responsible for collecting temperature and voltage values through artificial intelligence technology, and then transmits the collected values to the coordinator node responsible for collecting information, and sends the collected information to the PC through the serial port, and uses the serial port debugging tool to display collected data. Experimental data shows that signal attenuation gradually increases with distance, and distance and obstacles make it impossible to send data accurately. So you can add routing nodes to the network, add collectors and concentrators, and then add an enhanced RF (Radio Frequency Identification) generator to the antenna design. The experimental results show that in the case of two indoor walls and D≤20m, the signal strength is in the range of -82dBm to -94dBm, which can ensure the normal communication of data. If D≥25m, data communication cannot be guaranteed. By combining power and the Internet of Things, power-based Internet of Things can be built to comprehensively enhance power operations.